The Impact of Sales Growth, Financial Distress, Fixed Asset Intensity and Inventory Intensity on Tax Avoidance - Rahman Lasandang, Alifka Julraida; Benarda (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2026)
Taxes are often considered a burden that reduces profits, thus encouraging tax avoidance practices. The non-cyclical consumer sector is a vital source of tax, but is vulnerable to profit fluctuations and asset manipulation. The purpose of this study is to examine the effect of Sales Growth, Financial Distress, Fixed Asset Intensity, and Inventory Intensity on Tax Avoidance. The method used is a quantitative approach and purposive sampling, this study analyzed 31 non-cyclical consumer companies on the IDX for the 2019-2023 period with 155 samples using EViews 12 software. The results of this study partially, Sales Growth has a significant negative effect and Fixed Asset Intensity has a significant positive effect on Tax Avoidance. Financial Distress and Inventory Intensity have no significant effect. Simultaneously, all variables affect Tax Avoidance. Contribution: This study supports Agency Theory related to the internal drive of tax strategies and helps tax authorities map corporate tax reporting risks.